Designing an Information Technology Platform for Imparting Entrepreneurship Values in Social-Emotional Learning for Kindergarten Children Using EFA and CFA - Muji, Anggarda Paramita; Bentri, Alwen; Jamaris, Jamaris; Rakimahwati, Rakimahwati; Hidayati, Abna (Society of Visual Informatics, 2024)
Kindergarten is crucial for today's education. Kindergarten helps kids develop in all areas. Students work in groups on a simple project task in this study. The work includes topic-related activities. Kids should learn early on that being an entrepreneur will shape their identity & future. This condition makes someone realize that their long-term desire to be an entrepreneur comes from their academic success. This study investigated how the 35 questions are assembled & what improves them. 195 kindergarten teachers participated in the study. The sample was analyzed using EFA & CFA. Exploratory factor analysis revealed twelve unknown variables. The above variables explained 80% of the variation. Various factors explained the remaining 20%. All Cronbach's alpha values exceed requirements. CR >.7 & AVE >.5, indicating credible & tested constructs. The EFA showed that 195 research samples were sufficient because the KMO was above 0.50. This allowed more research. Six-factor solutions explained over 80.71% of the variation, so the EFA liked them. These factors kept the results consistent with those of previous studies. These traits facilitate legislator-educator dialogue rather than kindergarten teacher business observation. Researchers can use these properties for cluster analysis or multivariate linear regression. This subject requires more research because students develop a structured approach. Furthermore, experts should examine the research on what is making kindergarten entrepreneurship instruction popular.